Angiotensin II type 1 receptor overexpression in podocytes induces glomerulosclerosis in transgenic rats - Hoffmann, Sigrid; Podlich, Dirk; Hähnel, Brunhilde; Kriz, Wilhelm; Gretz, Norbert (Journal of the American Society of Nephrology, 2004)
ABSTRACT. Angiotensin II (AngII) is a critical determinant of glomerular function involving both hemodynamic and pressure-independent effects that are insufficiently understood. A novel transgenic rat (TGR) model with overexpression of the human AngII type 1 receptor (hAT1) in podocytes was developed to study the consequences of an increased AT1 signaling on the structure and function of the glomerular filter. Use of the nephrin promoter to target the podocytes resulted in an expression of the hAT1 at a level roughly two times higher than the endogenous AT1 throughout life. All male TGR developed significant albuminuria starting at 8 to 15 wk of age; systolic BP was not elevated. More or less concurrently, structural changes at the glomerulus were encountered, starting with ubiquitous formation of pseudocysts at podocytes, followed by foot process effacement and local detachments. This damage progressed to nephron loss via the well known pathway typical for classic focal segmental glomerulosclerosis. The structural changes significantly correlated with age (r2 = 0.76) and urinary albumin excretion (r2 = 0.70). The data provide direct evidence that increased AT1 signaling in podocytes leads to protein leakage and structural podocyte damage progressing to focal segmental glomerulosclerosis.
Gesehen am 22.06.2022